Purchasing, Sales and Inventory Information System Analysis and Design at Bahorok Indah Service - Alexander, Wilson; Ricky; Hanes; Joosten (Talenta Publisher, 2022)
Bahorok Indah Service is a motorcycle service and repair store that sells motorcycle parts and performs motorcycle repair. In carrying out its business process, Bahorok Indah Service still has not used a computerized system and some of the problems faced by the store are there is no detailed records of supplier, the store has difficulty determining the amount of stock to be purchased, no detailed records of stock amount, no information on the rack placement of stock and no motorcycle service records The system design can answer store problems with supplier list per stock form and stock per supplier form, minimum stock reports, inventory reports, rack number information and motorcycle service history on customer, sales and service forms.The results of this design can be further developed into a sofware